СУЛТОН САИДХОН ҲУКМРОНЛИГИ ДАВРИДА ФАРҒОНА ВОДИЙСИ (Scientific journal of the Fergana State University, 2023)
In this article on the base of  historical sources the issues of the ending of the state of Sultan Sayidkhan in Fergana valley and final establishment of power of Sheybanyds dynasty are researched.